Strategies for dementia prevention: latest evidence and implications. (August 2017) - Rakesh, Gopalkumar; Szabo, Steven T.; Alexopoulos, George S.; Zannas, Anthony S.
Dementia is a common and debilitating syndrome with enormous impact on individuals and societies. Preventing disease onset or progression would translate to public health and societal benefits. In this review, we discuss the latest evidence on interventions that may show promise for the prevention of cognitive decline. We appraise existing evidence primarily drawn from randomized controlled trials, systematic reviews, and meta-analyses, but also highlight observational studies in humans and relevant work in model organisms. Overall, there is currently limited evidence to support a cause–effect relationship between any preventive strategy and the development or progression of dementia. However, studies to date suggest that a multifactorial intervention comprising regular exercise and healthy diet, along with the amelioration of vascular risk factors, psychosocial stress, and major depressive episodes may be most promising for the prevention of cognitive decline. We discuss the challenges, future directions, and implications of this line of research.